PENGARUH PENGGUNAAN WEBSITE â€œZALORA.CO.IDâ€ TERHADAP MINAT BELANJA ONLINE DI KALANGAN KARYAWAN MNC MEDIA - Margaretha Megawindriati Mahawan; Siti Meisyaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
In Indonesia, the increasing number of internet users, encourage the businesses compete to take advantage of a website. In this study, a website which is used as a marketing medium is the website â€œzalora.co.idâ€. However, making a website as a marketing medium is not enough. Party founder of the website â€œzalora.co.idâ€ must be able to manage their website, to create the impression of quality and credibility. Thus, could affect the interest of websiteâ€™s users to buy fashion products. The purpose of this study is to determine user assessment to the quality of information in the website â€œzalora.co.idâ€, capable of affecting the interest of online shopping among MNC Media employees from redaction division of Sindo Newspaper.This research is related to the application of broadcasting study. So the researches make communication technology, cyber media, websites, interactive communications, uses and gratification theory, and interest, as a part of the theoretical foundation.In this study, researchers used quantitative research methods and descriptive. After distribute the questionnaire and get the results of the questionnaire, the researchers test the validity and reliability data. Through the results of the data analysis, the researchers got the conclusions that the respondentsâ€™ assessment of the quality of the website which is represented by the indicator of the variable X, namely the use of website â€œzalora.co.idâ€, affecting online shopping interest among MNC Media employees of redactional division from Sindo Newspaper.Â Keywords: Online Shopping, Communication Technology, Interactive Communications